EFFECT OF TOCOPHEROL, TREHALOSE AND SOIL IMPROVEMENT IN WATER PRODUCTIVITY AND INDUSTRIAL POTATOES UNDER WATER STRESS - AbdulKarim H. Sh. Al-Rubaie; Kadhim D. H. Al-Jubouri (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to investigate the impact of tocopherol, trehalose and soil improvement in water productivity and industrial potatoes (Solanum tuberosum L.), Austin hybrid. The field experiments were carried out during the fall season 2020-2021 and spring season 2021. The experiments were carried out as a factorial experiment within a split plot design. The irrigation interval factor was set every 4, 8 and 12 days for the fall season 2020-2021 and every 4, 7 and 10 days for the spring season 2021 (symbolized by I0, I1 and I2) in the main plot, and the interaction factor between Eco Gel soil improvement and anti-stress spray in the Sub plot with three replications. a Eco Gel was added to the soil at the level of 50 kg ha-1 symbolized by E1 and added to the level of 100 kg ha-1 symbolized by E2 as well as the treatment without adding that Its symbol is E0, and spraying with anti-stress, spraying tocopherol at a concentration of 30 mg L-1, symbolized by T1, and spraying trehalose with a concentration of 30 mmol L-1 and symbolized by T2, in addition to spraying with ordinary water, symbolized by T0, the results showed a significant superiority for the treatment of the triple interaction I1E2T2 in the leaf area, the total chlorophyll concentration, the dry weight of the vegetative and the number of marketable tubers The marketable plant yield, the total marketable yield, the relative water content of leaf, the leaf water potential, and the water productivity for the two seasons respectively,compared to treatment I2E0T0.